Common Challenges to the Development of Novel Antivirals to Tackle Re-emerging Infections of Pandemic Potential - Wu, Yu; Hu, Shuo; Liu, Feng (Archives of Clinical and Biomedical Research, 2026)
Herpesviruses, HIV, Ebola virus, influenza viruses and flaviviruses like dengue virus (DENV) continue to pose a global threat due to their capacity for rapid genetic evolution. As the molecular arms race escalates, technology-driven antiviral discovery is central to modern preparedness. Emerging innovations now complement traditional direct-acting antivirals that target virus-encoded proteins and broad-spectrum agents that modulate shared viral and host pathways. High-throughput screening platforms, AI-enabled drug discovery engines, and computational protein–ligand modeling are also accelerating the identification of antiviral agents at an unprecedented speed. Drug repurposing, supported by machine learning-driven prediction of off-target antiviral activity is now a strategy in outbreak settings where clinical trial windows are compressed. Beyond small molecules, programmable RNA therapeutics, CRISPR-based antivirals, engineered peptide inhibitors, and monoclonal/bi-specific antibodies are redefining therapy. Despite these advances, significant challenges remain. Viral diversity means that resistance can emerge rapidly, meaning broad-spectrum activity without compromising safety remains challenging. These issues are beginning to be addressed through genomic surveillance networks, integrated clinical trial platforms, and globally coordinated research ecosystems. To strengthen global health resilience, future antiviral programs will require expanded investment in next-generation technologies, automation-assisted drug discovery pipelines, and scalable manufacturing/stockpiling systems. This review uses four exemplar viruses namely herpesviruses, DENV, Ebola virus, and influenza virus to outline common technological challenges and highlight the innovative strategies shaping the next era of antiviral development.